jurnal Analisis dan Pengembangan Tata Kelola Teknologi Informasi pada Kantor POS Kotabumi Menggunakan COBIT 2019: Analysis and Development of Information Technology Governance at the Kotabumi POS Office Using COBIT 2019 - Wahyudi; Sutedi (Jurnal Sistem Informasi, 2025)
Analysis of process maturity in various organizational domains shows significant progress in operational effectiveness and management. Assessments were carried out on sub-processes in the MEA, DSS, DSS04, and DSS05 domains, with a focus on financial reporting accuracy, decision making, customer service, risk management, and operational efficiency. The results show that many processes are at a good level of maturity, with some sub-processes reaching the highest level of optimization. Although there are areas for improvement, particularly in internal communications and planning, the organization shows great potential for further development and improved performance in the future.   Keywords: Process maturity, operational efficiency, decision making, risk management, customer satisfaction